Antidiabetic, cytotoxic and antioxidant activities of oil extracted from Acrocomia aculeata pulp. Issue 16 (18th August 2019) - da Silva, Perla V. B.; Ramiro, Marianne M.; Iriguchi, Edna K. K.; Corrêa, William A.; Lowe, Jennifer; Cardoso, Claudia A. L.; Arena, Arielle C.; Kassuya, Cândida A. L.; Muzzi, Rozanna M.
Abstract: This study evaluated the hypoglycemic effect of the oil extracted from the Acrocomia aculeata pulp (OPAC) in normoglycemic rats and streptozotocin (STZ), fructose-induced diabetic rat models and its in vitro antioxidant and cytotoxic potential. OPAC (3, 30 or 300 mg/kg, v.o.) significantly decreased ( p  < 0.05) the high glucose levels induced by a high fructose-diet in rats. Persistent treatment with OPAC for 24 days also reduced the high plasmatic glucose induced by STZ. In normoglycemic animals, OPAC significantly decreased glucose levels. While A. aculeata oil exhibited good in vitro antioxidant activity, no sign of cytotoxicity was observed in LLC-PK1 cells (5–500 μg/mL). OPAC has antidiabetic and antioxidant activities without causing in vitro cytotoxicity. Abstract :